SERUM IMMUNOGLOBULIN G, M AND A LEVELS IN CHILDREN WITH NEPHROTIC SYNDROME AND ITS CORRELATION WITH BIOCHEMICAL PARAMETERS - Ammar B. Al-Assadi, Nidhal A. Mohammed and Shatha H. Ali (Pakistan Journal of Biotechnology, 2018)
Nephrotic syndrome (NS) is an immune-mediated renal disease that linked with T-cells dysfunction and secondary disturbance of B-cells with changes in concentration of immunoglobulin (Ig). The aim of this study is to compare the levels of IgG, IgM, and IgA in children with nephrotic syndrome and healthy control children. Fifty children with NS were divided into four groups: fourteen steroids sensitive infrequent relapse (SSIFR), twelve steroid sensitive frequent relapse (SSFR), nine steroid resistance (SR) and fifteen newly diagnosed nephrotic syndrome (ND) compared to twenty-five unrelated healthy children. Results of IgG, IgM and IgA serum levels determined by RID showed a significant decrease (P=0.0001) in IgG mean level (464.72 ± 50.34 mg/dl) of NS children in compared with healthy control mean level (1209.34 ± 75.51 mg/dl), and a highly significant increase (P=0.0001) in IgM mean level (201.37 ± 10.12 mg/dl) of NS patients in compared with control mean level (113.08 ± 8.42 mg/dl), there is no significant difference (P=0.4387) between NS patients and healthy control in IgA serum levels. In all children with NS, in comparison to healthy control, the serum level of IgG is reduced and the serum level of IgM is elevated. There is a close relation between albuminuria, hypoalbuminemia and hyperlipidemia and serum IgG and IgM levels. There is no significant difference between IgA level in patients and control